β-adrenergic receptor responsiveness in aging heart and clinical implications - Ferrara, Nicola; Komici, Klara; Corbi, Graziamaria; Pagano, Gennaro; Furgi, Giuseppe; Rengo, Carlo; Femminella, Grazia Daniela; Leosco, Dario; Bonaduce, Domenico (Frontiers in Physiology, 2014)
Elderly healthy individuals have a reduced exercise tolerance and a decreased left ventricle inotropic reserve related to increased vascular afterload, arterial-ventricular load mismatching, physical deconditioning and impaired autonomic regulation (the so called “β-adrenergic desensitization”). Adrenergic responsiveness is altered with aging and the age-related changes are limited to the β-adrenergic receptor density reduction and to the β-adrenoceptor-G-protein(s)-adenylyl cyclase system abnormalities, while the type and level of abnormalities change with species and tissues. Epidemiological studies have shown an high incidence and prevalence of heart failure in the elderly and a great body of evidence correlate the changes of β-adrenergic system with heart failure pathogenesis. In particular it is well known that: a) levels of cathecolamines are directly correlated with mortality and functional status in heart failure, b) β1-adrenergic receptor subtype is down-regulated in heart failure, c) heart failure-dependent cardiac adrenergic responsiveness reduction is related to changes in G proteins activity. In this review we focus on the cardiovascular β-adrenergic changes involvement in the aging process and on similarities and differences between aging heart and heart failure.